IL-28B genotypes as predictors of long-term outcome in patients with hepatitis C-related severe liver injury - Jelena Jordovic; Jasmina Simonovic-Babic; Vladimir Gasic; Nikola Kotur; Branka Zukic; Sonja Pavlovic; Ivana Lazarevic; Danijela Karalic; Natasa Katanic; Natasa Nikolic; Aleksandar Urosevic; Jelena Nestorov; et al. (Journal of Infection in Developing Countries)
Introduction: Patients with severe fibrosis or cirrhosis are at high risk for liver-related complications, even after successful antiviral treatment and/or regression of fibrosis. These are the first published results concerning the role of IL-28B genotypes as predictors of the durability of sustained virological response (SVR) and long-term outcome, in patients with baseline severe fibrosis and cirrhosis caused by hepatitis C (HCV) infection.